Pleural effusion in a Labrador Retriever puppy. Case report - Vanegas-Alonso, B. (2024)
The therapeutic approach of a Labrador Retriever canine patient who arrives at the clinic with respiratory difficulty, orthopneic position and abdominal pain is described. Paraclinical tests are performed such as a hemo-leucogram, finding a decrease in the red line and a marked leucocytosis. In the radiographic projections, an increase in the density of the right hemithorax is seen and the presence of free fluid is confirmed by ultrasonography in the intercostal window. A thoracentesis is performed to determine the type of fluid and its subsequent evacuation from the cavity.